NURSES KNOWLEDGE AND PRACTICE REGARDING THE PREVENTION OF SURGICAL SITE INFECTION AT TERTIARY CARE HOSPITALS IN LAHORE - KHALID , N; MANZOOR , M; FIRDOUS , U; KHAN , RA; SHOUKAT , S; ZAFA , S (Biological and Clinical Sciences Research Journal, 2023)
Surgical site infections (SSIs) are significant complications that can arise following surgical procedures, often due to lapses in surgical techniques or post-operative wound care. This study aimed to assess the level of knowledge and adherence to best practices among nurses in preventing surgical site infections (SSIs) within the complex healthcare environment of tertiary care hospitals in Lahore. A quantitative cross-sectional study design was employed to evaluate the knowledge and practices of nurses regarding SSI prevention. The research was conducted at two prominent healthcare institutions, the Services Institute of Medical Sciences (SIMS) and Lahore General Hospital (LGH). The findings of this study indicate that a substantial majority, exceeding 75% of the participants, exhibit commendable knowledge and practice in preventing surgical site infections at tertiary care hospitals in Lahore. In conclusion, the study underscores that many nurses within these tertiary care hospitals possess substantial knowledge and consistently adhere to best practices for preventing surgical site infections. This implies a promising preparedness and commitment to patient safety within this critical aspect of surgical care.